German perspectives on right-wing extremism : challenges for comparative analysis - Kiess, Johannes 1985- HerausgeberIn; Decker, Oliver 1968- HerausgeberIn; Brähler, Elmar 1946- HerausgeberIn (Routledge studies in extremism and democracy, 2016)
Introduction : German Perspectives on Right-Wing Extremism Challenges for Comparative Analysis / Johannes Kiess, Oliver Decker & Elmar Brähler -- Comparing Right-Wing Extremist Attitudes : Lack of Research or Lack of Theory? / Johannes Kiess & Oliver Decker -- Attitude and Agency : Common Roots, Divergent Methodologies, Joint Ventures / Katrin Reimer -- National Identity and Immigration in the Concepts of Right-Wing Extremism and Societal Security / Marc Grimm -- A Multi-Method Approach to the Comparative Analysis of Anti-Pluralistic Politics / Karin Liebhart -- "Fertile Soil for Ideological Confusion" : The Extremism of the Centre / Oliver Decker, Johannes Kiess & Elmar Brähler -- Fear of Social Decline and Treading on Those Below : The Role of Social Crises and Insecurities in the Emergence and the Reception of Prejudices in Austria / Julia Hofmann -- Terrorism Made in Germany : the Case of the NSU / Michael Edinger & Eugen Schatschneider -- Extremist or Populist? : Proposing a Set of Criteria to Distinguish Right-Wing Parties in Western Europe / Tanja Wolf